2014
DOI: 10.1080/00958972.2014.897338
|View full text |Cite
|
Sign up to set email alerts
|

Ether formation on the tridentate Schiff base ligands of copper(II) complexes

Abstract: A series of copper(II) complexes, CuL·imidazole, where L 2− are tridentate Schiff base ligands formed by condensation of salicylaldehyde with a series of amino acids, have been synthesized. Visible spectral data indicate that copper(II) in these complexes are five coordinate in the solid state and in solution. Electrospray mass spectrometry has been used to show how these complexes react in alcohol/NaOH solutions with and without the presence of D-galactose. In the absence of D-galactose where the amino acid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The use of mass spectrometry has been reported in a study of the oxidation of d-galactose (Gal) by Cu II complexes of a series of tridentate Schiff base ligands in alcohol/NaOH solutions (Butcher et al, 2014). The change in the color of the solutions from blue-green to yellow and the appearance of a negative-ion electrospray mass spectral peak at m/z = 195 [Oxidized Gal + OH] showed that the copper complexes had oxidized the galactose while being reduced to a Cu I species.…”
Section: Introductionmentioning
confidence: 99%
“…The use of mass spectrometry has been reported in a study of the oxidation of d-galactose (Gal) by Cu II complexes of a series of tridentate Schiff base ligands in alcohol/NaOH solutions (Butcher et al, 2014). The change in the color of the solutions from blue-green to yellow and the appearance of a negative-ion electrospray mass spectral peak at m/z = 195 [Oxidized Gal + OH] showed that the copper complexes had oxidized the galactose while being reduced to a Cu I species.…”
Section: Introductionmentioning
confidence: 99%